(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Nietzsche’s view of catharsis has attracted some but not a great deal of attention. Part of the reason is that he rarely makes use of the term itself, seemingly rejecting out of hand the Aristotelian-inspired theory of tragic catharsis. Catharsis would appear to be an unrewarding area for understanding Nietzsche. Nevertheless, The Birth of Tragedy appears to foreground Nietzsche’s rejection of tragic classical catharsis, and the book is surely about catharsis in this sense. However, a closer look at his works suggests that catharsis theory is always present. This article aims to explore Nietzsche’s understanding about catharsis and its importance in nowadays drama and tragedy studies.